Genetic engineering and the intrinsic value and integrity of animals and plants. - Heaf, David, ....-; Wirz, Johannes, ....- (Llanystumdwy : Ifgene, 2002)
What do we mean by the intrinsic value and integrity of plants andanimals? - Holmes Rolston IIIEngineering genesis - pioneering genetic engineering and ethics inScotland - Donald BruceSeeing the integrity and intrinsic value of animals: developingappreciative modes of understanding - Craig HoldregeDoes genetic engineering impact the intrinsic value and integrity ofplants? - Howard DaviesPhenomenological studies on transgenic potatoes: genetic modificationadds more than intended traits - Ruth RichterDoes genetic engineering impact the intrinsic value and integrity ofanimals? - Henk VerhoogDoes genetic engineering impact the intrinsic value and integrity ofanimals? - Harry GriffinWhy is it in the farmer's interest to pay attention to the intrinsicvalue and integrity of animals and plants? - Timothy BrinkNew rules for a new situation: protecting animals' interests in the eraof genetic engineering - Mike RadfordCould genetic engineering be part of a sustainable breeding approach? -Christina
HenatschNaturalness and breeding in organic farming - Ton BaarsThe socio-economic implications of biotechnology in agriculture:exploring the issues- Ben Davies, Caspian Richards & Clive L. SpashProgress towards a science of organisms: genetically modified animals -Bruce WhitelawTowards a science of organism: lessons to learn from phenomenology -Johannes WirzMaking a social contract for biotechnology - Donald BruceGenetic engineering and intrinsic value: the New Zealand experience -Alastair S. Gunn and Kelly A. TudhopeThe relation between ethics and aesthetics in connection with moraljudgements about gene technology - Michael HauskellerMaize landrace integrity and transgenic introgression: the recent Mexicanexperience - Fernando Ortiz MonasterioExperts and the public assessing intrinsic ethical concerns: experienceswith the Dutch animal biotechnology policy - Lino PaulaSubstantial equivalence and ethical equivalence: contrasting approaches -Sylvie PouteauThe intrinsic value of micro-organisms
- Judyth Sassoon.
Proceedings of a workshop at the Royal Botanic Garden, Edinburgh, UK, 18-21 september 2002
Keywords: Biotechnologie; Genetische manipulatie